Understanding the Challenges of Hashimoto's Thyroiditis: Perspectives on Diagnosis, Treatment, and Associated Conditions - Klaudia Brygida Kułak; Karolina Palacz; Katarzyna Gadżała; Izabela Janik; Marzena Pliszka; Katarzyna Chamera-Cyrek; Anna Maria Koman (Kazimierz Wielki University, 2024)
Introduction: Hashimoto's thyroiditis is a prevalent autoimmune disease among the population. With the progress in diagnostic and research techniques, it has come to light that Hashimoto's thyroiditis is linked to a higher likelihood of developing other disorders that impact multiple organs and systems. Throughout the course of this disease, individuals may experience an array of complications such as sexual dysfunctions, fertility problems, specific mental disorders, cardiovascular diseases and other autoimmune diseases. Aim of the Study: The primary aim of this study is to explore the potential association between Hashimoto's thyroiditis and its consequential effects on other physiological systems and organs. Description of the State of Knowledge: Hashimoto's thyroiditis is a complex autoimmune disease characterized by chronic inflammation of the thyroid gland. The pathogenesis of the disease is not yet completely understood. Hashimoto's thyroiditis has been associated with a range of health issues, including sexual dysfunction, fertility problems, psychiatric disorders, cardiovascular diseases, and other autoimmune disorders. Materials and methods: An unsystematic scientific literature review was conducted using specific keywords such as Hashimoto's thyroiditis, fertility problems, thyroid tumor, cardiovascular diseases, and autoimmune diseases. The review was carried out on PubMed, analyzing a total of 53 sources published until 2023. Conclusions: HT's association with psychiatric disorders, fertility issues, thyroid tumors, cardiovascular dysfunction, and comorbid autoimmune conditions underscores its broad clinical impact, necessitating integrated management approaches. Effective management of HT requires collaboration among specialists to ensure early detection, proactive intervention, and patient education, ultimately improving therapeutic outcomes and quality of life.